MRI safety, imaging artefacts, and grid distortion evaluated for FFP3 respiratory masks worn throughout the COVID-19 pandemic. Issue 8 (August 2022) - Keenan, B.E.; Lacan, F.; Cooper, A.; Evans, S.L.; Evans, J.
Abstract : AIM: To determine which filtering face piece (FFP3) respirators worn throughout the COVID-19 pandemic are safe for magnetic resonance imaging (MRI). MATERIALS AND METHODS: Three clinical MRI sequences were performed to assess imaging artefacts, grid distortion, and local heating for eight commercially available FFP3 respirators. All examinations were performed at Cardiff University Brain Research Imaging Centre using a 3 T Siemens Magnetom Prisma with a 64-channel head and neck coil. Each FFP3 mask was positioned on a custom-developed three-dimensional (3D) head phantom for testing. RESULTS: Five of the eight FFP3 masks contained ferromagnetic components and were regarded as "MRI unsafe". One mask was considered "MRI conditional" and only two masks were deemed "MRI safe" for both MRI staff and patients. Temperature strips positioned at the nasal bridge of the phantom did not exhibit local heating. A maximum grid distortion of 5 mm was seen in the anterior portion of the head of the ferromagnetic FFP3 masks. CONCLUSION: This study has demonstrated the importance of assessing respiratory FFP3 masks for use in and around MRI machines. Future research involving FFP3 masks can be conducted safely by following the procedures laid out in this study. Highlights: There is limited information regarding MR safety for respirators. Eight commercially available FFP3 masks were evaluated for MR safety at 3T. Five of the eight masks contained ferromagnetic components and are 'MR Unsafe'. Geometric distortion was seen in the 'MR Unsafe' masks. Any future MR studies involving respirator masks must undergo MR safety evaluation.